2017
DOI: 10.1093/annonc/mdx305
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of PD-L1 testing on the cost-effectiveness and economic impact of immune checkpoint inhibitors for the second-line treatment of NSCLC

Abstract: The use of PD-L1 expression as a biomarker increases cost-effectiveness of immunotherapy but also diminishes the number of potential life-years saved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 26 publications
2
76
2
1
Order By: Relevance
“…This analysis is subject to certain limitations. First, we were unable to estimate costs for immunotherapy drugs, which have shown promising gains in survival for some patients, because approvals for lung cancer treatment came after the end of our study period . Second, the SEER‐Medicare data used in our analysis were limited to patients over age 65 who were not simultaneously enrolled in managed care and we were unable to determine the proportion of patient‐liability costs paid out of pocket vs the portion paid by purchased Medigap coverage.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis is subject to certain limitations. First, we were unable to estimate costs for immunotherapy drugs, which have shown promising gains in survival for some patients, because approvals for lung cancer treatment came after the end of our study period . Second, the SEER‐Medicare data used in our analysis were limited to patients over age 65 who were not simultaneously enrolled in managed care and we were unable to determine the proportion of patient‐liability costs paid out of pocket vs the portion paid by purchased Medigap coverage.…”
Section: Discussionmentioning
confidence: 99%
“…All these data are listed in Table 1. 16,[19][20][21][22][23][28][29][30][31][32] For dosage calculation in the United States and China, body surface area (BSA) and body weight of 1.84 m 2 , 71.4 kg and 1.72 m 2 , 65 kg were adopted respectively. [33][34][35]…”
Section: Health Care Resource Uses Costs and Utilitymentioning
confidence: 99%
“…IL-35 inhibited PD-L1 under metabolic deprivation in ADC tumour cell line As described above and indicated in the literature, IFNγ, a potent anti-tumour cytokine, induced PD-L1 in A549 that points out to a double role of this cytokine in tumour because anti-PD-L1 trial has demonstrated to be successful in some cases of NSCLC. 7,28 However, ADC is also signed by genetic imprints that must be considered, such as the expression of the epidermal growth factor receptor (EGFR) which binds to EGF, a potent growth factor for the ADC. [29][30][31] Therefore, we next asked whether IL-35 would regulate these pathways under growth factor deprivation.…”
Section: Il-35 Regulation Of Nsclc Cell Survivalmentioning
confidence: 99%